Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norge og polarområdene - Hansson, Rasmus (ed.) (Utenriksdepartementet, 1998)
Keywords: Antarktis; Norge; geografi; historie; miljøvern; polarforskning; polarområdene; politikk

Large spatial variation in accumulation rate in Jutulstraumen ice stream, Dronning Maud Land, Antarctica - Melvold, Kjetil; Hagen, Jon Ove; Pinglot, Jean Francis; Gunuestrup, Niels (Annals of Glaciology, 1998)
A mass-balance programme was initiated on Jutulstraumen ice stream, western Dronning Maud Land,Antarctica, during the austral summer 1992-93. As a part of the mass-balance programme, accumulation rate was measured along the centre line of Jutulstraumen from the shelf edge up to the plateau at about 2500 m a.s.l. Accumulation distribution obtained from seven shallow firn cores and 48 slake readings is presented. The overall net accumulation trend displays a decreasing accumulation with increasing elevation and distance to coast, but on both the mesoscale and microscale there are significant variations. This is due to complex patterns of precipitation controlled by orography and redistribution by katabatic winds. The local accumulation distribution (few km scale) was found to be dependent on downslope surface gradient (aspect north, northwest), and variations up to 100% were found over distances of less than 3 km. The large variation in accumulation is important when selecting new core sites and for interpretation of temporal and spatial variations in accumulation derived from firn cores.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; geofysikk; geografi; glasiologi; isstrøm

Kvitkuven: Kronprinsesse Märtha Kyst (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet B6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet C7S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet B7S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Ahlmannryggen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Pages: Blad/Sheet G5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Pages: Blad/Sheet G6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Using multiple data sources to enhance photogrammetry for mapping Antarctic terrain - Fox, Adrian J (Polar Research, 1995)
Keywords: Antarktis; flyfoto; geografi; kartlegging; luftfoto; satellittbilder

Geographical discoveries in Antarctica by the whaling industry - Headland, Robert Keith (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Antarktis; Carl Anton Larsen; Lars Christensen; ekspedisjoner; geografi; hvalfangst; oppdagelsesreiser

Nature environment map: Gjelsvikfjella and Western Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica - Høgvard, K (Norsk Polarinstitutt, 1993)
Pages: Blad/Sheet 1 Publication Title: Norsk Polarinstitutt Temakart Nr. 24 Place: Oslo
Keywords: Dronning Maud Land; NARE 1984/85; NARE 1989/90; geografi; kartlegging

Jutulsessen: Fimbulheimen (Norsk Polarinstitutt, 1992)
Place: Oslo
Keywords: Dronning Maud Land; Troll forskningsstasjon; geografi; kartlegging; satellite bilder

H.U. Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad H6S Place: [Oslo]
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad/Sheet H5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad/Sheet J5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad/Sheet J6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Heimfrontfjella Nord: Maudheimvidda (Norsk Polarinstitutt, 1988)
Pages: Blad/Sheet D8 Place: Oslo
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Heimfrontfjella Sør: Maudheimvidda (Norsk Polarinstitutt, 1988)
Pages: Blad/Sheet D9 Place: Oslo
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Namnemanus Peter I Øy (Norsk Polarinstitutt, 1988)
Pages: Vedtak sak 125, 21.1.1988. Namnekomiteen
Keywords: Peter I. Øy; geografi; kartlegging

Norway's polar territories - Barr, Susan (Aschehoug, 1987)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Peter I. Øy; geografi; geologi; historie; polarområdene; polarpolitikk

Flichnerfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1984)
Pages: Blad/Sheet K5 Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Norge i polarområdene - Egeland, Knut (Leif Holtedahls forl., 1982)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Forposten: Fimbulheimen (Norsk Polarinstitutt, 1975)
Pages: Blad/Sheet N5 Place: Oslo
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Sarkofagen: Fimbulheimen (Norsk Polarinstitutt, 1975)
Blad/Sheet N6
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Schirmacheroasen: Fimbulheimen / Prinsesse Astrid Kyst (Norsk Polarinstitutt, 1973)
Pages: Blad/Sheet L4
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Starheimtind: Fimbulheimen / Prinsesse Astrid Kyst (Norsk Polarinstitutt, 1973)
Blad/Sheet M4
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Annandagstoppane. Maudheimvidda (Norsk Polarinstitutt, 1972)
Pages: Blad E6 Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1972)
Pages: Blad/Sheet C7 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1972)
Pages: Blad/Sheet B7 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Humboldtfjella: Fimbulheimen (Norsk Polarinstitutt, 1968)
Blad/Sheet L5
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Wohlthatmassivet: Fimbulheimen (Norsk Polarinstitutt, 1968)
Blad/Sheet M5
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Erobringen av Antarktis - Harstad, Herlof (Aschehoug, 1968)
Keywords: Antarktis; Sydpolen; biografier; ekspedisjoner; geografi; historie; oppdagelsesreiser; polarekspedisjoner

Filchnerfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1966)
Blad/Sheet K5
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Mühlig-Hofmannfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1966)
Blad/Sheet J5
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Glopeflya: Fimbulheimen (Norsk Polarinstitutt, 1964)
Blad/Sheet L6
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Hoelfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1964)
Blad/Sheet M6
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Sydishavet og tilgrensende områder: Blad 11 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1964)
Place: Sandefjord
Keywords: Norsel (skip); Sørishavet; geografi; kartlegging

Kronprinsesse Märtha Kyst - Maudheimvidda: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Place: [Oslo]
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Maudheimvidda Aust: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

In Amundsen's Tracks on the Axel Heiberg Glacier - Herbert, Walter William (The Geographical Journal, 1963)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Borgmassivet: Maudheimvidda (Norsk Polarinstitutt, 1962)
Pages: Blad/Sheet F6 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Filchnerfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1962)
Blad/Sheet K6
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Giæverryggen: Maudheimvidda (Norsk Polarinstitutt, 1962)
Pages: Blad/Sheet F5 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Mühlig-Hofmannfjella Sör: Fimbulheimen (Norsk Polarinstitutt, 1962)
Blad/Sheet J6
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Ahlmannryggen: Fimbulheimen (Norsk Polarinstitutt, 1961)
Blad/Sheet G5
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

H.U.Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1961)
Blad/Sheet H6
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1961)
Blad/Sheet H5
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1961)
Blad/Sheet H5
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1961)
Blad/Sheet G6
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Kirwanveggen: Maudheimvidda (Norsk Polarinstitutt, 1961)
Blad/Sheet F7
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Neumayerskarvet: Maudheimvidda (Norsk Polarinstitutt, 1961)
Blad/Sheet G7
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Dronning Maud Land: Sør-Rondane - Luncke, Bernhard (Norsk Polarinstitutt, 1957)
Place: [Oslo]
Keywords: Antarktiske ekspedisjon 1946-47; Dronning Maud Land; Richard Evelyn Byrd; flyfoto; geografi; kartlegging; luftfoto

Femti år for Kongen - Riiser-Larsen, Hjalmar (Gyldendal, 1957)
Keywords: Antarktis; Hjalmar Riiser; Larsen; biografier; ekspedisjoner; geografi; kartlegging; luftfart; oppdagelsesreiser; polarforskning; polarområdene

Air operations of the Norwegian-British-Swedish Antarctic Expedition in 1952 - Essen, Reinhold von (Polar Record, 1956)
Publisher: Cambridge University Press
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; flyfoto; forskning; geografi; luftfoto

Harpuner og mannfolk : fra en fangstferd i Antarktis - Ree, Ørnulf (A.S Sæbbøs, 1953)
Keywords: Sørishavet; geografi; historie; hvalfangere; hvalfangst

Maudheim : to år i Antarktis : den norsk-britisk-svenske vitenskapelige ekspedisjon til Antarktis 1949-1952 - Giæver, John (Gyldendal, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); ekspedisjoner; forskning; forskningsstasjoner; geografi; historie; oppdagelsesreiser; overvintring; sjøreiser

A Radar Survey of the Ice Barrier - Higgins, Robert (Journal of Navigation, 1952)
Publisher: Cambridge University Press
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geografi; geologi

Sydishavet: Blad 2 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1950)
Place: Sandefjord
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; geografi; kartlegging

Sydishavet og tilgrensende farvann: Blad 12 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1949)
Place: Sandefjord
Keywords: Sørishavet; geografi; hvalfangst; kartlegging

Antarktis - Luncke, Bernhard (Norges Svalbard- og ishavs-undersøkelsers kartarbeider og anvendelsen av skrå-fotogrammer tatt fra fly, 1949)
Keywords: Antarktis; geografi; kartlegging

Antarktis/Antarctica: Kart nummer 7 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Place: Sandefjord
Keywords: Antarktis; Lars Christensen; ekspedisjoner; flyfoto; geografi; kartlegging; luftfoto

Sydishavet (Blad 5) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Place: Sandefjord
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 7) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Place: Sandefjord
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 8) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Place: Sandefjord
Keywords: Sørishavet; geografi; kartlegging

Roald Amundsens opdagelsesreiser - Amundsen, Roald (Gyldendal, 1942)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; geografi; historie; oppdagelsesreiser

Bouvet-Insel - Engelmann, Gerhard (Geographische Zeitschrift, 1940)
Publisher: Franz Steiner Verlag
Keywords: Bouvetøya; geografi; historie

Det Norske Geografiske Selskap (The Geographical Journal, 1939)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Det Norske Geografiske Selskap; ekspedisjoner; geografi; polarområdene

Recent Reconnaissance Flights in the Antarctic - Christensen, Lars (The Geographical Journal, 1939)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjon; flyfoto; geografi; hvalfangere; hvalfangst; luftfoto; oppdagelsesreiser

The Course of Antarctic Exploration between Longitudes 20° W. and 110° E. Notes on the map compiled to accompany the paper by Mr. Lars Christensen - Christensen, Lars (The Geographical Journal, 1939)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Lars Christensen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Min siste ekspedisjon til Antarktis 1936-1937: med en oversikt over forskningsarbeidene på ferdene 1927-1937 - Christensen, Lars (Tanum, 1938)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Odd I; Sydpolen; Thorshavn ekspedisjoner; geografi; hvalfangere; hvalfangst

Sydishavet - Balleny öyene (Blad 3) (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 3 Place: Sandefjord
Keywords: Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet - Hearst Land, Charcot ö (Blad 4) (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 4 Place: Sandefjord
Keywords: Norvegia ekspedisjoner; Peter I. Øy; Sørishavet; geografi; kartlegging

Sydishavet - Kong Haakon VII Hav (Blad 1) (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; Thorshammer ekspedisjon; geografi; kartlegging

Sydishavet - Kronprins Olav Land (Blad 2) (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 2 Place: Sandefjord
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; Thorshavn ekspedisjon; geografi; kartlegging

Sydishavet (Blad 6) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 6 Place: Sandefjord
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 7) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 7 Place: Sandefjord
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 8) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 8 Place: Sandefjord
Keywords: Sørishavet; geografi; kartlegging

Antarktis og Sydishavet (Norwegian Mapping Authority / Kartverket, 1936)
Keywords: Antarktis; Jason ekspedisjonene; Norvegia ekspedisjoner; Odd I; Sørishavet; Thorshavn ekspedisjon; ekspedisjonen; geografi; kartlegging

Sydishavet (Blad 1) (Hvalfangernes Assuranceforening, 1936)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; geografi; kartlegging

Tilsjøs under napoleonskrigene : en norsk sjømanns opplevelser 1802-1854 - Eide, Henrik O (Aschehoug, 1936)
Keywords: Sørishavet; biografi; ekspedisjoner; fangst; geografi; historie; sjøfolk; skippere

Modifications des Noms de lieu du Continent Antarctique - Hansen, Hans Edvard (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1936)
Publisher: Routledge
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjon; flyfoto; geografi; kartografi; luftfoto; oppdagelsesreiser

Bunnen av Weddellhavet (Hvalfangernes Assuranceforening, 1935)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet (Blad 2) (Hvalfangernes Assuranceforening, 1935)
Pages: Blad 2 Place: Sandefjord
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sørishavet; Thorshavn ekspedisjon; geografi; kartlegging

Sydishavet - Weddel Havet - Kong Haakon VII hav (Blad 1) (Hvalfangernes Assuranceforening, 1935)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Opdagelsen Av Ingrid Christensen Land - Mikkelsen, Klarius (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1935)
Publisher: Routledge
Keywords: Antarktis; Ingrid Christensen Land; Thorshavn ekspedisjon; geografi; kartlegging; kartografi; oppdagelsesreiser

Norvegia rundt sydpollandet : Norvegia-ekspedisjonen 1930-1931 - Isachsen, Gunnar (Gyldendal, 1934)
Publication Title: Publikasjon fra Kommandør Chr. Christensens hvalfangstmuseum i Sandefjord
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; Sydpolen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

Sydishavet (Blad 2) (Hvalfangernes Assuranceforening, 1933)
Pages: Blad 2 Place: Sandefjord
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet (Blad 3) (Hvalfangernes Assuranceforening, 1933)
Pages: Blad 3 Place: Sandefjord
Keywords: Antarktis; Sørishavet; ekspedisjoner; geografi; kartlegging

Sydishavet - Weddel Havet - Kong Haakon VII hav (Blad 1) (Hvalfangernes Assuranceforening, 1933)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Norwegian Explorations in the Antarctic, 1930-1931 - Isachsen, Gunnar (Geographical Review, 1932)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjoner; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

Relation of the Work of the Mawson and Norwegian Antarctic Expeditions, 1930-1931 - Joerg, Wolfgang Louis Gottfried (Geographical Review, 1932)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjoner; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Antarctic Circumnavigation by the "Norvegia" (Geographical Review, 1931)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; polarområdene

Norvegia-ekspedisjonen 1930-1931 (Norges geografi oppmåling, 1931)
Pages: 5 kart Place: [S.l.]
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet - Kong Haakon VII hav (Norges geografi oppmåling, 1931)
Place: [S.l.]
Keywords: Antarktis; Sørishavet; ekspedisjoner; geografi; kartlegging

Antarctic Research by the Norvegia Expeditions and Others - Holtedahl, Olaf (The Geographical Journal, 1931)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Lars Christensen; Norvegia ekspedisjonene; Odd I.; Sørishavet; ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

I. Norske undersøkelser ved Sydpollandet 1929-1931. II. Norvegia-ekspedisjonen 1930-1931 : omseilingen av Sydpollandet - Isachsen, Gunnar (1931)
Publication Title: Meddelelser
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; Sydpolen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

Den Tredje »Norvegia«-Ekspedisjon 1929—1930 - Riiser-Larsen, Hjalmar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1930)
Publisher: Routledge
Keywords: Bouvetøya; Hjalmar Riiser; Larsen; Norvegia ekspedisjonen; geografi; kartlegging

Mot ukjent land : Norvegia-ekspedisjonen 1929-1930 - Riiser-Larsen, Hjalmar (Gyldendal, 1930)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; lutfart; oppdagelsesreiser

The "Norvegia" Antarctic Expedition of 1929-1930 - Riiser-Larsen, Hjalmar (Geographical Review, 1930)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; lutfart; oppdagelsesreiser

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Publisher: Routledge
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

[Kart over Antarktika og Sydishavet]. Skisser med "Odd" og "Norvegia" sine ruter i Antarktis 1927-1929 - [Aagaard, Bjarne] (1929)
Keywords: Antarktis; Norvegia ekspedisjoner; Odd I; Sørishavet; ekspedisjonen; geografi; kartlegging

Peter I Øy - Larsen, Nils (1929)
Pages: ved Nils Larsen, Norvegia-Ekspedisjonen 1928-1929 Place: Oslo
Keywords: Lars Christensen; Norvegia ekspedisjonen; Peter I. Øy; geografi; kartlegging

Die norwegische Bouvetinsel - Sachse, Walter (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1929)
Publisher: Perthes Place: Gotha
Keywords: Bouvetøya; Norvegia ekspedisjoner; geografi; oppdagelsesreiser

Die norwegische Peter-I.-Insel - Sachse, Walter (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1929)
Publisher: Perthes Place: Gotha
Keywords: Odd I; Peter I. Øy; ekspedisjonen; geografi; oppdagelsesreiser

The "Norvegia"-expedition and Bouvet Island - Aagaard, Bjarne (Norges Handels og Sjøfartstidende, 1928)
Keywords: Antarktis; Bouvetøya; Lars Christensen; Norvegia ekspedisjonen; ekspedisjoner; geografi; historie; internasjonal; politikk; rett

James Cook - Haffner, Einar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Det er i år 150 år siden James Cook døde. Der er så mange jubileer og minnefester i våre dager at man undertiden synes det kan bli litt for meget av det gode. Men de efterfølgende minneord er helliget en mann som ingen der er geografisk interessert, nogensinde bør glemme.
Publisher: Routledge
Keywords: James Cook; Sørishavet; geografi; oppdagelsesreiser; polarekspedisjoner; polarfarere

Fra det norske forskningsarbeide i de vest-antarktiske strøk syd-sommeren 1927—28 - Holtedahl, Olaf (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Publisher: Routledge
Keywords: Lars Christensen; Odd I; Peter I. Øy; ekspedisjonen; geografi; kartlegging

The Norwegian South Polar Expedition - Amundsen, Roald (The Geographical Journal, 1913)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; ekspedisjoner; geografi; oppdagelsesreiser; polarområdene

Amundsen`s Attainment of the South Pole (The National geographic magazine, 1912)
Publisher: National Geographic Society
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Amundsen's Expedition to the South Pole (Bulletin of the American Geographical Society, 1912)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Sydpolen: den norske sydpolsfærd med Fram 1910-1912 - Amundsen, Roald (Jacob Dybwads forl., 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Sydpolen: den norske sydpolsfærd med Fram 1910-1912 - Amundsen, Roald (Jacob Dybwads forl., 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

The South Pole : an account of the Norwegian Antarctic expedition in the "Fram" 1910-1912 - Amundsen, Roald (Murray, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

The South Pole : an account of the Norwegian Antarctic expedition in the "Fram" 1910-1912 - Amundsen, Roald (Murray, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Amundsen`s Antarctic Explorations - Brown, R N Rudmose (Scottish Geographical Magazine, 1912)
Publisher: Routledge
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Nærmest Sydpolen : Aaret 1900 - Borchgrevink, Carsten Egeberg (Gyldendal, 1905)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

The "Southern Cross" Expedition to the Antarctic, 1899-1900 - Borchgrevink, Carsten Egeberg (The Geographical Journal, 1900)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Southern Cross; biologi; ekspedisjonen; ekspedisjoner; forskning; geografi; meteorologi; oppdagelsesreiser; overvintring; zoologi